Carbon dioxide reforming of methane over ruthenium substituted strontium titanate perovskite catalysts - Gurav, Hanmant R.; Bobade, Richa; Das, Vineetha Lakshmi; Chilukuri, Satyanarayana V. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Strontium titanate (SrTiO3) doped with varying amounts of ruthenium (7.9, 15.6 and 31 wt%) have been prepared by the citrate gel synthesis method. Structural and textural characterizations reveal that at lower concentrations, a major part of Ru is incorporated in the lattice of SiTiO3. The content of surface Ru (outside lattice) increases with increasing amounts of the doped Ru. The surface Ru reduced at lower temperatures compared to Ru incorporated into the lattice. The reduction of the lattice substituted Ru occurs only at temperatures above the collapse of the perovskite structure. The catalyst sample with 7.9 wt% of Ru shows good conversions in the dry reforming of methane with CO2. The conversion of CO2 is in excess compared to methane under the studied reaction conditions. As a result, H-2/CO ratio of the product gases which should have been equivalent to unity is lower than the stoichiometric value. This ratio is particularly low when lower reaction temperatures (873-973 K) were used. Similar was the case when high space velocities were used. Low methane conversion and reverse water gas shift reaction are the causes for the low H-2/CO ratios.
Keywords: Carbon dioxide reforming; Catalysts; Citrate gel method; Doped catalysts; Dry reforming; Methane reforming; Perovskites; Reverse water gas shift; Ruthenium doped catalysts; Strontium titanate; Syngas